2009
DOI: 10.18553/jmcp.2009.15.4.344
|View full text |Cite
|
Sign up to set email alerts
|

Results of an Intervention in an Academic Internal Medicine Clinic to Continue, Step-Down, or Discontinue Proton Pump Inhibitor Therapy Related to a Tennessee Medicaid Formulary Change

Abstract: indication for PPI therapy and acid suppression therapy was discontinued (discontinue therapy group), 40 (31.0%) met the TennCare PA criteria for continuation of PPI therapy (PA group), and 71 (55.0%) did not meet the TennCare PA criteria and were stepped down to a H2-blocker (step-down group). At the 8-month follow-up, acid suppression therapy was assessed in 68 patients (21 patients were lost to follow-up): 13 patients (19.1%) had resumed PPI therapy; 38 (55.9%) were using an H2-blocker; and 17 (25.0%) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…38 However, very few research studies have examined the extent to which the clinical guidelines 39 are being followed in the UK [14][15][16][17][18][19] . The aim of this study was to determine the prevalence of 40 PPI use and assess the practices employed to reduce PPI use in the general UK population. It 41 is anticipated that research of this nature will help to inform future attempts to moderate the 42 use of PPIs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…38 However, very few research studies have examined the extent to which the clinical guidelines 39 are being followed in the UK [14][15][16][17][18][19] . The aim of this study was to determine the prevalence of 40 PPI use and assess the practices employed to reduce PPI use in the general UK population. It 41 is anticipated that research of this nature will help to inform future attempts to moderate the 42 use of PPIs.…”
mentioning
confidence: 99%
“…Previous studies [36][37][38][39] reported discontinuation rates that differed from those 236 identified in our study; however, these can be explained by variations in the study population 237 and the discontinuation strategies employed 38 . Reports regarding the outcomes of step-238 down therapy have been conflicting 40,41 . For example, one study reported that more than 239 half of the patients involved in the study remained asymptomatic after the step down 41 while 240 another reported that 19% of patients whose PPI therapy was stepped down experienced 241 relapsed symptoms and resumed PPI use 40 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27][28] Other studies have demonstrated the cost effectiveness and improvement in patient self-reported GERD symptoms with on-demand and intermittent PPI dosing. [29][30][31] Fewer data have been produced regarding the impact of clinical pharmacists, in an ambulatory care setting, on the reduction of chronic PPI use in patients without indication for long-term therapy.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Many previous studies utilized a follow-up period of 6-12 months. 23,24,26,27 Due to the fact that the follow-up period was shortened by 2 months, a greater portion of this period represented the actual taper process; thus, we postulated that the PPM count at follow-up may have been higher than what would have resulted if the follow-up period remained 5 months. Patients on the highest dose of a twice-daily PPI may have required upwards of 3 months before being transitioned to a H2RA.…”
Section: Limitationsmentioning
confidence: 99%